Statistical comparison of results of problem solutions for the fifth grade mathematics olympiads - Kanišauskienė, Karolina (Lietuvos matematikos rinkinys, 2022)
The article presents a comparable analysis of the results of solving problems in Šiauliai city (the 2nd Stage) mathematics olympiads for the 5th grade students throughout 2016–2019. It aims to find out whether school students selected for olympiads at different times are characteristic of similar giftedness, to ascertain that the level of difficulty of problems to be solved does not always reflect their diagnostic informativity and to try to divide schools to clusters according to students who participated in olympiads and their results.
Keywords: clusters; mathematics olympiad; statistical analysis